Exponential tracking control of an electro-pneumatic servo motor - Lazić, Dragan V. (Strojniški vestnik, 2008)
According to the fundamental importance of the tracking theory on technical systems, the main goal of this paper is a further development of the theory and the application of the tracking, especially to the practical tracking concept. The new definition of the practical exponential tracking is shown. The practical tracking is defined by the output vector, which is different from the former definitions, given by the output error vector. The defined exponential tracking is elementwise. The new criterion of the practical exponential tracking is shown. Based of the new criteria, the control algorithm of practical exponential tracking is determined by using the self-adaptive principle. The structural characteristic of such a control system is the existence of two feedback sources: the global negative of the output value and the local positive of the control value. Such a structure ensures the synthesis of the control without the internal dynamics knowledge and without measurements of disturbance values. The plant under consideration is an electro-pneumatic servo motor. This system is often applied as the finalcontrol element of a controller in automatic control systems. The correction device for the mentioned plant will be a digital computer. The mentioned control forces the observed plant output to track the desired outputvalue with prespecified accuracy. In this paper the simulation results produced by practical tracking control algorithm on an electro-pneumatic servosystem will be presented. The results show a high quality of the practical exponential tracking automatic control. The type of the control ensures the change of the output error value according to a prespecified exponential law.
Keywords: nelinearni sistemi; elektropnevmatika; servo motorji